Uji Efektivitas Antibakteri Ekstrak Daun Sirih Hijau (Piper Betle L.) Terhadap Pertumbuhan Bakteri Staphylococcus Aureus - Sucipto, Ajeng Afriliana; Dwiningrum, Riza; Wibowo, Catur Ari; Suswidiantoro, Vicko (Peneliti.net, 2025)
This research is at testing the effectiveness of a variable a laboratory experimental research with a disc diffusion method on nutrient agar media with 5 treatments in the form of negative control, positive control, 40% betel leaf extract, 50% betel leaf extract, and 60% betel leaf extract. Data analysis was carried out with the Kruskal Wallis test then continued with the Post Hoc test with the Mann Whitney test. The Kruskal Wallis test results obtained a significance value of 0.020 value (sig) <0.05, so it can be said that there is a significant difference in the average diameter of the inhibition zone between the treatment groups. The Mann Whitney test results show a value (sig) > 0.05 for positive control, concentrations of 40%, 50% and 60% have significant effectiveness against the growth of Staphylococcus aureus bacteria. In this study, 40% concentration has an average value of 18.87 mm with a standard deviation of 2.13 mm, 50% concentration has an average value of 19.75 mm with a standard deviation of 4.58 mm, and 60% concentration has an average value of 19.87 mm and a standard deviation of 2.13 mm which shows that it is included in the strong category. T his shows that green betel leaves (Piper betle L.) can be used as an antibacterial.